Risco nutricional, sintomas de impacto nutricional e fatores associados em pacientes com câncer de cabeça e pescoço - Soares, Louise Vasconcelos de Oliveira (2024)
Introduction: According to the National Cancer Institute, malignant neoplasia is the main public health problem worldwide. Malnutrition is a common finding in head and neck cancer (HNC), and factors such as tumor location, treatments used, side effects, and disease stage directly or indirectly affect nutritional status. Early detection of nutritional risk and nutritional impact symptoms (NIS) can lead to better nutritional status and more favorable clinical outcomes. Objective: To identify factors associated with nutritional risk and assess whether NIS, measured by the Head and Neck Symptoms Checklist (HNSC), are significant determinants of nutritional risk according to the Nutritional Risk Screening (NRS-2002) in patients with HNC. Method: This is a cross-sectional study involving 132 patients with HNC from a reference oncology hospital in Vitória. Data collection took place between September 2022 and January 2024, shortly after the diagnosis was confirmed. A questionnaire was administered, including sociodemographic variables, lifestyle habits, and dietary changes. Anthropometric assessment, nutritional risk screening using NRS-2002, and SIN screening using HNSC were performed. Results: Among the participants, 46.2% were found to be at nutritional risk. It was observed that a household income of up to 2 minimum wages increased the chances of developing nutritional risk by 2.9 times (OR = 2.916; 95% CI = 1.017-8.359; p = 0.046). Additionally, each centimeter increase in calf circumference (CC) reduced the chances of nutritional risk by 24.9% (OR = 0.751; 95% CI = 0.646-0.873; p < 0.001). Patients with an income ≤ 2 minimum wages had a 0.54 point increase in NRS-2002 score compared to those with an income > 2 minimum wages (p = 0.026). Regarding NIS, each point in the dysphagia score (p = 0.002) and olfactory alteration (p = 0.024) increased the NRS score by 0.19 points. Conclusion: Individuals with low income are more likely to be at nutritional risk, while those with a higher CC have a reduced risk, highlighting these factors as critical determinants of the nutritional status of HNC patients. Additionally, socioeconomic profile and NIS, such as dysphagia and olfactory alteration, are crucial factors for increasing nutritional risk in the pre-treatment period.